Allelopathy of Panicum maximum Jacq. on Euphorbia heterophylla L. and Amaranthus dubius Mart. in laboratory - Alonso Sánchez, Lisette (2023)
Introduction. Delving into the allopathic effects of weeds on agricultural crops and other weeds is of great importance in establishing management strategies. Objective. To evaluate the allelopathic effect of residues fromPanicum maximum Jacq. rhizomes on Euphorbia heterophylla L. and Amaranthus dubius Mart. in pre and postemergence.Materials and methods. Four experiments were conducted in completely randomized design 5x5 at the Plant Health Laboratory in Cienfuegos, Cuba, in 2020. The allelopathic capacity of P. maximum rhizome residuesagainst E. heterophylla and A. dubius was evaluated in pre-emergence and post-emergence applications. Five treatments were assessed: 0, 40, 60, 80, and 100 g of P. maximum plants rhizomes fractioned per 2 kg of soil, with five repetitions (plastic pots). Rhizomes were obtained from plants in the flowering and fruiting stage at three months of age. At 12 days from the treatment, the percentage of emergence and/or survival, radicle, and hypocotyl length were compared. Analysis of variance and mean comparisons using Tukey’s test (p≤0.05) were performed using SPSS (vers. 15). Results. When comparing the treatment effect against E. heterophylla, a significant reduction in emergence in pre-emergence and a decrease in survival percentage and hypocotyl length in post-emergence were observed, whileagainst A. dubius, there was a reduction in emergence and survival, and a significant decrease in radicle and hypocotyllength pre and post-emergence. Conclusions. The negative allelopathic effect (P<0.05) of P. maximum residues onboth E. heterophylla and A. dubius was confirmed.